Preparation and piezoelectric electro-catalysis application of molybdenum disulfide coated barium titanate nano material

The synthesis of molybdenum disulfide-coated barium titanate nanomaterials by hydrothermal method solved the problem of insufficient barium titanate energy band structure and piezoelectric photocatalytic performance, and significantly improved the efficiency of piezoelectric photosynthesis and hydrogen production.

CN119702009APending Publication Date: 2025-03-28HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411908851.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The energy band structure and piezoelectric photocatalytic properties of barium titanate limit the piezoelectric photosynthesis and the efficiency of hydrogen production.

Method used

Molybdenum disulfide coated barium titanate nanomaterials by hydrothermal method to form heterojunctions to enhance the light absorption capacity and piezoelectric properties of the material.

Benefits of technology

The light absorption characteristics of the material in the visible light region are significantly improved, and the efficiency of piezoelectric photoelectric synergistic catalytic degradation of organic pollutants and hydrogen production is enhanced, reaching 2.3 and 1.9 times that of pure phase molybdenum disulfide and barium titanate, respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005205105540000011
    Figure HDA0005205105540000011
  • Figure HDA0005205105540000012
    Figure HDA0005205105540000012
  • Figure HDA0005205105540000021
    Figure HDA0005205105540000021
Patent Text Reader

Abstract

The invention relates to preparation of a molybdenum disulfide coated barium titanate nano material and application of the molybdenum disulfide coated barium titanate nano material in the field of piezoelectric light concerted catalysis. Compared with pure-phase MoS2 and BaTiO3, the molybdenum disulfide coated barium titanate nano material synthesized by a hydrothermal method shows a remarkably enhanced piezoelectric optical effect. Under the synergistic effect of ultrasound and light, the molybdenum disulfide coated barium titanate nano material can realize efficient degradation of rhodamine B and remarkable improvement of hydrogen production efficiency, the degradation rate constants are 2.3 and 14.4 times of those of pure-phase MoS2 and BaTiO3 respectively, and the hydrogen production efficiency is 2.3 and 1.9 times of those of pure-phase MoS2 and BaTiO3 respectively. The piezoelectric catalyst BaTiO3 and the photocatalyst MoS2 can be well combined to form a heterojunction, so that the electron-hole separation efficiency is improved. The invention discloses a method for improving the production of hydrogen by degrading rhodamine B and decomposing water by the material by constructing the heterojunction, and the method is simple in process flow, high in operability and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] This article belongs to the field of piezoelectric photocatalytic technology, and specifically involves the preparation of a molybdenum disulfide-coated barium titanate nanomaterial and the application of the composite material in piezoelectric photocatalytic degradation of pollutants and hydrogen production. Background technology:

[0002] The continued growth of the global population has led to increased industrialization, exacerbating environmental issues related to water, air, and soil pollution. Improper treatment of industrial wastewater has become a pressing global issue. Green and efficient cleaning methods, including photocatalysis, electrocatalysis, and photoelectrocatalysis, are being adopted to address these challenges. Photocatalysts that can harness solar energy have received considerable attention in water purification applications.

[0003] Hydrogen energy has become a promising alternative due to its cleanness, high efficiency and ease of handling, storage and transportation. Photocatalytic hydrogen production has broad prospects in terms of economic benefits, energy conservation and sustainable production of clean energy. The controlled synthesis of nanorods, nanospheres and other nanostructures allows precise manipulation of their optical, electronic and catalytic properties to improve photocatalytic performance. These materials exhibit strong light absorption, effective charge separation and increased surface reactivity, which can more effectively utilize solar energy and promote the generation of active species for photocatalytic reactions. Piezoelectric semiconductors, as emerging materials, use the additional driving force of the polarization field (ultrasonic vibration, stirring, etc.) to promote the transport of photogenerated charges to improve catalytic efficiency. Piezoelectric photocatalysis, as an emerging advanced oxidation technology, can collect and utilize solar energy and natural mechanical energy (i.e., hydrodynamic energy) to achieve the generation of reactive oxygen species, which plays a key role in the removal of pollutants. At present, piezoelectric photosynthetic catalysis technology mainly focuses on two aspects: 1) improving efficiency by adjusting the macroscopic polarization of a single piezoelectric semiconductor; 2) constructing piezoelectric heterostructures by coupling with other semiconductors or precious metals. In addition, under the simultaneous action of ultrasonic vibration and light, the piezoelectric potential of the piezoelectric heterojunction can prevent the shielding of the polarization field by the photogenerated charges. Most importantly, the internal polarization field caused by the piezoelectric response and the interfacial electric field at the heterojunction interface can synergistically promote charge transfer and separation, thus producing an excellent synergistic effect in the piezoelectric-assisted photocatalytic system.

[0004] Perovskite metal oxide barium titanate (BaTiO 3 , referred to as BTO), exhibits excellent electronic and optical properties, as well as high photochemical stability and efficient catalytic performance as a photocatalyst. However, BaTiO 3 It is a semiconductor with a relatively wide bandgap, limited response to visible light, and a high recombination rate of photogenerated electrons and holes, which limits its widespread application.

[0005] Molybdenum disulfide (MoS2 MoS (abbreviated as MS) is another narrow bandgap semiconductor with a high specific surface area and abundant active sites, which is beneficial to the photocatalytic process. 2 The band gap of MoS is in the range of 1.2 to 1.9 eV, making it a promising candidate for chemical modification. 2 Combined with other semiconductors, the efficiency of hydrogen production is improved. 2 @BaTiO 3 (MB for short) heterojunction can not only effectively reduce electron-hole recombination but also possess excellent conductivity and active edge sites. Summary of the invention:

[0006] The technical problem to be solved by the present invention is that the piezoelectric photocatalytic degradation of organic pollutants and the piezoelectric photocatalytic hydrogen production efficiency are low due to the limitations of the energy band structure and piezoelectric photocatalytic performance of barium titanate. At present, the modification of piezoelectric semiconductor materials and photocatalytic semiconductor materials to form a heterojunction is one of the main methods to improve material performance. 3 Usually has a wide band gap and is mainly activated by non-visible light; while MoS 2 It is a two-dimensional sheet with a smaller size, deposited on BaTiO 3 The surface of the nanorods acts as a light absorbing component, thereby improving the utilization efficiency of the composite material across the entire solar spectrum. 3 A piezoelectric potential is generated inside the nanorods, which promotes the separation of photogenerated carriers and enhances the piezoelectric-photosynergistic catalytic ability of the composite material.

[0007] The present invention discloses a preparation method and piezoelectric-photocatalytic application of a molybdenum disulfide-coated barium titanate nanomaterial, which mainly involves the preparation and characterization of a molybdenum disulfide-coated barium titanate nanomaterial, and the research on the piezoelectric-photocatalytic degradation of organic pollutants and hydrogen production of the nanomaterial, which is specifically carried out by the following steps:

[0008] Step 1, weigh 20.0-25.0g of sodium hydroxide and 0.8-1.0g of titanium dioxide, respectively, dissolve and disperse them in 50ml of distilled water, and form a uniform solution by ultrasonication; stir at room temperature for 2 hours, transfer the mixed solution to the lining of the reactor for hydrothermal reaction, and centrifuge the turbid liquid after the hydrothermal reaction to obtain a certain amount of precipitate;

[0009] Step 2: Soak the precipitate obtained in step 1 in a dilute hydrochloric acid solution for 8 hours, then centrifuge and wash with water three times, and finally wash with ethanol and vacuum dry to obtain H 2 Ti 3 O 7 powder;

[0010] Step 3: Weigh 0.15-0.2g of the powder obtained in step 2 and 0.3-0.5g of barium hydroxide octahydrate, disperse and dissolve them in 50ml of distilled water, and form a uniform solution by ultrasonication; transfer the mixed solution to the lining of the reactor for hydrothermal reaction, and centrifuge the turbid liquid after the hydrothermal reaction to obtain a certain amount of precipitate;

[0011] Step 4: Soak the precipitate obtained in step 3 in a dilute hydrochloric acid solution for 8 hours, then centrifuge and wash with water three times, and finally wash with ethanol, and vacuum dry to obtain barium titanate nanomaterials;

[0012] Step 5: Dissolve 0.3-0.4g sodium molybdate and 0.7-0.8g thiourea in 80ml distilled water, and form a uniform transparent colorless solution by ultrasonication. Add the barium titanate powder obtained in step 4, stir for 1.5 hours, adjust the pH, transfer the mixed solution to the lining of the reactor for hydrothermal reaction, and centrifuge the turbid liquid after the hydrothermal reaction to obtain a certain amount of precipitate.

[0013] Step 6: Wash the precipitate obtained in step 5 with water, centrifuge, alternately three times, and finally wash with ethanol, and vacuum dry to obtain a molybdenum disulfide-coated barium titanate nanocomposite material.

[0014] The hydrothermal reaction temperature in step 1 is 180-200° C., preferably 200° C.; the hydrothermal reaction time is 18-24 h, preferably 24 h.

[0015] The hydrothermal reaction temperature in step 3 is 180-220° C., preferably 210° C.; the hydrothermal reaction time is 85 min.

[0016] The hydrothermal reaction temperature in step 5 is 180-220° C., preferably 220° C.; the hydrothermal reaction time is 24-30 h, preferably 30 h.

[0017] The pH value of step 5 is adjusted to 0.5-2, preferably 1.5.

[0018] The centrifugal speed described in steps 1, 2, 3, 4, 5 and 6 is 9000 r / min.

[0019] The vacuum drying conditions described in steps 2, 4 and 6 are: temperature of 50 to 70° C., preferably 60° C.; vacuum degree of -25 to -30 kPa, preferably -30 kPa; time of 9 to 14 h, preferably 12 h.

[0020] Step 7: Application of molybdenum disulfide-coated barium titanate nanomaterials in piezoelectric photocatalytic degradation of organic pollutants. The specific operation steps are as follows: evenly disperse the molybdenum disulfide-coated barium titanate nanomaterials in an organic pollutant Rhodamine B aqueous solution, and stir in the dark to achieve adsorption and desorption equilibrium. Under the conditions of mechanical force and light, measure the absorbance change of the Rhodamine B aqueous solution by a liquid ultraviolet visible spectrophotometer, and finally calculate the degradation rate of the Rhodamine B aqueous solution.

[0021] Step 8: Application of MoS2-coated Barium Titanate Nanomaterials in Piezoelectric Photocatalytic Water Decomposition to Generate Hydrogen. The specific steps are as follows: First, MoS2-coated Barium Titanate Nanomaterials are evenly dispersed in a triethanolamine aqueous solution, and then the mixed solution is poured into a sealed container, nitrogen is introduced, and oxygen is excluded. Under the combined action of mechanical force and light, the amount of hydrogen generated is measured by gas chromatograph.

[0022] The concentration of the Rhodamine B (RhB) solution in step 7 is 20 mg / L.

[0023] The mechanical force and light described in steps 7 and 8 are specifically generated by the following method: subjecting the reaction solution containing the molybdenum disulfide-coated barium titanate nanomaterial to ultrasound and xenon lamp irradiation.

[0024] Preferably, the ultrasonic frequency is 20-60 kHz, more preferably 40 kHz; the xenon lamp power is 100-500 W, preferably 300 W, and the filter is λ>420 nm.

[0025] The present invention characterizes the molybdenum disulfide-coated barium titanate nanomaterial and tests its piezoelectric photocatalytic performance by using an X-ray powder diffractometer, a transmission electron microscope, a fluorescence spectrometer, and an ultraviolet-visible spectrophotometer.

[0026] Advantages and effects of the present invention:

[0027] The present invention is simple to operate. By hydrothermally synthesizing molybdenum disulfide-coated barium titanate nanomaterials, the heterojunction-modified barium titanate can not only form a piezoelectric field under the action of mechanical force, provide driving force for photoinduced charges and holes, enhance separation, and inhibit recombination, but also the hydrothermal method synthesized nanocomposite materials have better uniformity and dispersibility. By optimizing the pH value conditions and the content of barium titanate in the molybdenum disulfide preparation precursor solution during the synthesis process, the molybdenum disulfide-coated barium titanate composite nanomaterial with the best performance is obtained. Due to the presence of molybdenum disulfide, the material exhibits good light absorption characteristics in the visible light region, and can achieve maximum utilization of the sunlight spectrum. The experimental results show that the optimized MoS2-coated Barium Titanate nanomaterial has excellent performance in the piezoelectric photocatalytic degradation of Rhodamine B. It can degrade 95.2% of the high-concentration Rhodamine B solution (20 mg / L) within 60 min, and its rate constant k value is 2.3 and 14.4 times that of pure MoS2 and Barium Titanate, respectively. In terms of piezoelectric photocatalytic hydrogen production, the hydrogen production within 4 hours is about 8716.28 μmol·g -1 , which are 2.3 and 1.9 times that of pure phase molybdenum disulfide and barium titanate, respectively, effectively improving the degradation efficiency of organic pollutants and hydrogen production. Description of the drawings:

[0028] Figure 1 X-ray powder diffraction patterns of MoS2-coated barium titanate nanomaterials and pure phase MoS2 and barium titanate nanomaterials

[0029] Figure 2 Transmission electron microscopy image of molybdenum disulfide coated barium titanate nanomaterial

[0030] Figure 3 UV-visible diffuse reflection absorption spectra of MoS2-coated barium titanate nanomaterials and pure MoS2 and barium titanate nanomaterials

[0031] Figure 4 Fluorescence spectra of MoS2-coated barium titanate nanomaterials and pure MoS2 and barium titanate nanomaterials

[0032] Figure 5 The dotted line graph shows the comparison of the piezoelectric catalytic degradation rate of molybdenum disulfide coated barium titanate nanomaterials with different barium titanate addition amounts.

[0033] Figure 6 The dotted line graph shows the comparison of the piezoelectric photocatalytic degradation rate of MoS2-coated barium titanate nanomaterials with different barium titanate addition amounts.

[0034] Figure 7 The dotted line graph shows the comparison of the piezoelectric photocatalytic hydrogen production of MoS2-coated barium titanate nanomaterials and pure MoS2 and barium titanate nanomaterials. Specific implementation method:

[0035] Implementation 1:

[0036] Step 1, dissolve and disperse 20g of sodium hydroxide and 0.8498g of titanium dioxide in 50ml of distilled water respectively, and form a uniform solution by ultrasonic treatment; stir at room temperature for 2 hours, transfer the mixed solution to the lining of the reactor and perform hydrothermal reaction at 200°C for 30 hours, centrifuge the turbid liquid after the hydrothermal reaction to obtain a certain amount of precipitate;

[0037] Step 2: Soak the precipitate obtained in step 1 in a dilute hydrochloric acid solution (0.2 mol / L) for 8 hours, then centrifuge and wash with water three times, and finally wash with ethanol, and vacuum dry at 60°C for 12 hours to obtain H 2 Ti 3 O 7 powder;

[0038] Step 3: Weigh 0.15 g of the powder obtained in step 2 and 0.3674 g of barium hydroxide octahydrate, respectively disperse and dissolve them in 50 ml of distilled water, and form a uniform solution by ultrasound; transfer the mixed solution to the inner lining of the reactor and perform a hydrothermal reaction at 210° C. for 85 min, centrifuge the turbid liquid after the hydrothermal reaction, and obtain a certain amount of precipitate;

[0039] Step 4: After centrifuging the precipitate obtained in step 3, immersing it in a dilute hydrochloric acid solution (0.2 mol / L) for 8 hours, then centrifuging the obtained product, washing it with water, alternating three times, and finally washing it with ethanol, and vacuum drying it at 60° C. for 12 hours to obtain a barium titanate nanomaterial;

[0040] Step 5: Dissolve 0.362 g of sodium molybdate and 0.726 g of thiourea in 80 ml of distilled water, and form a uniform transparent colorless solution by ultrasonication. Add 25.56 mg of the barium titanate powder obtained in step 4, and stir for 1.5 hours. Adjust the pH to 1.5, transfer the mixed solution to the inner lining of the reactor, and perform a hydrothermal reaction at 220° C. for 24 hours. Centrifuge the turbid liquid after the hydrothermal reaction to obtain a certain amount of precipitate.

[0041] Step 6: Wash the precipitate obtained above with water, centrifuge it, alternately three times, and finally wash it with ethanol, and vacuum dry it at 60° C. for 12 hours to obtain a molybdenum disulfide-coated barium titanate nanocomposite material;

[0042] Step 7, weigh 25 mg of the molybdenum disulfide-coated barium titanate nanomaterial obtained above and evenly disperse it into 25 ml of 20 mg / L RhB solution, stir in the dark to reach adsorption and desorption equilibrium, and then measure the absorbance change of the RhB solution by UV-visible spectrophotometer under ultrasonic vibration and light from the 0th minute, once every 10 minutes, for a total of 60 minutes;

[0043] Step 8: Take 5 mg of the molybdenum disulfide-coated barium titanate nanomaterial obtained above and evenly disperse it in 100 ml of 20% by volume triethanolamine solution; in a sealed reactor, first introduce nitrogen for 30 minutes to remove oxygen, and then under ultrasonic vibration and light conditions, measure the amount of hydrogen generated above the reactor every hour starting from the 0th hour, and continue measuring for 4 hours.

[0044] The following test was used to verify the effect of the invention:

[0045] 1. Preparation and characterization of MoS2-coated barium titanate nanomaterials

[0046] The crystal phase structures of the prepared molybdenum disulfide-coated barium titanate nanomaterials and pure phase barium titanate and molybdenum disulfide nanomaterials were characterized by X-ray powder diffraction (XRD). Figure 1 The XRD patterns of MoS2-coated barium titanate nanomaterials and pure phase MoS2 and Barium titanate nanomaterials are shown in the figure, corresponding to the standard cards of MoS2 (PDF#01-075-1539) and Barium titanate (PDF#00-005-0462). As shown in the figure, the diffraction peaks of MoS2-coated barium titanate nanomaterials at 2θ=14.0°, 33.3° and 59.0° correspond to the (002), (100) and (110) crystal planes of MoS2, respectively, while the diffraction peaks of Barium titanate are not obvious, which may be caused by the small amount of Barium titanate added. The XRD diffraction patterns of MoS2 and Barium titanate nanomaterials are consistent with the standard PDF cards, and no other impurities appear.

[0047] The morphology of the prepared MoS2-coated Barium Titanate nanomaterials was observed by transmission electron microscopy. Figure 2 As shown, the prepared MoS2 coated Barium Titanate nanomaterial has a rod-like morphology with a diameter of about 500nm. Compared with Barium Titanate, the crystal shape does not change much after coating, and they are all nanorods.

[0048] The absorption characteristics of MoS2-coated Barium Titanate nanomaterials and pure MoS2 and Barium Titanate nanomaterials in the visible light range were studied by UV-visible diffuse reflectance absorption spectroscopy (UV-vis DRS). Figure 3 As shown, barium titanate nanomaterials are wide-bandgap semiconductors with almost no visible light absorption; molybdenum disulfide exhibits high light absorption capacity in the visible light range; in the composite system, the addition of molybdenum disulfide significantly enhances the absorption in the visible light region.

[0049] The migration and recombination process of photogenerated carriers in MoS2-coated BaTiO3 nanomaterials and pure MoS2 and BaTiO3 were studied by comparing the fluorescence spectra (PL). Figure 4As shown, the PL intensity of MoS2-coated barium titanate nanomaterials is significantly lower than that of pure MoS2 and barium titanate. This fluorescence quenching phenomenon indicates that the recombination of photogenerated electrons and holes in the prepared MoS2-coated barium titanate nanomaterials has been effectively suppressed.

[0050] 2. Study on catalytic degradation efficiency

[0051] The degradation performance of MoS2-coated barium titanate nanocomposites with different barium titanate additions was compared by UV spectrophotometer to find the best composite ratio. Figure 5 The performance comparison of composite materials (respectively MB-5, MB-10 and MB-15) with different amounts of barium titanate added under ultrasonic vibration (40kHz) is shown. The experimental results show that MB-10 composite nanomaterial has the best catalytic degradation performance.

[0052] Figure 6 The results show the piezoelectric photocatalytic degradation effect of molybdenum disulfide-coated barium titanate nanomaterials with different barium titanate addition amounts and pure molybdenum disulfide and barium titanate nanomaterials on the organic pollutant Rhodamine B within 60 minutes. Specifically, during the 60-minute degradation experiment, MB-5, MB-10, MB-15 composite nanomaterials and pure molybdenum disulfide and barium titanate nanomaterials achieved Rhodamine B degradation rates of 51.4%, 95.2%, 82.2%, 74.6% and 19.1%, respectively. At the same time, by comparing the degradation rate constant k value, it can be found that the rate constant k value of the MB-10 composite nanomaterial (0.02679min -1 ) is significantly higher than MB-5 (0.0064min -1 )、MB-15(0.01488min -1 ) and pure molybdenum disulfide (0.01167min -1 )、barium titanate (0.00186min -1 ) nanomaterials, even reaching 14.4 times that of barium titanate. This result shows that MB-10 composite nanomaterials have higher degradation efficiency and reaction rate in degrading organic pollutants.

[0053] 3. Study on hydrogen production performance

[0054] The invention patent uses gas chromatograph to detect the hydrogen production performance of molybdenum disulfide, barium titanate and molybdenum disulfide coated barium titanate nanomaterials under ultrasonic vibration and light conditions. The experiment was carried out for 4 hours under ultrasonic vibration (40kHz) and xenon lamp irradiation (300W) environment. Figure 7The results show that under the conditions of mechanical vibration (40kHz) and xenon lamp irradiation (300W), the hydrogen production of pure molybdenum disulfide and barium titanate nanomaterials in 4 hours is only 3791.76.4μmol·g -1 、4526.14μmol·g -1 In comparison, under the same conditions, the composite material produced about 8716.28 μmol·g hydrogen in 4 hours. -1 , which is about 2.3 and 1.9 times the hydrogen production of pure molybdenum disulfide and barium titanate nanomaterials. This result fully demonstrates that molybdenum disulfide-coated barium titanate nanomaterials have significant advantages in hydrogen production efficiency.

[0055] In summary, the present invention successfully synthesized molybdenum disulfide-coated barium titanate nanomaterials by a hydrothermal method using sodium hydroxide, titanium dioxide, sodium molybdate and thiourea as reactants. The experimental results show that molybdenum disulfide-coated barium titanate nanomaterials show significant improvements in both piezoelectric-photosynergistic catalytic degradation and hydrogen production performance. This study provides valuable insights into the design of unique heterostructures for simultaneous photocatalytic degradation of pollutants and hydrogen evolution, and has broad application prospects in various environmental and energy-related fields.

Claims

1. Preparation of a molybdenum disulfide-coated barium titanate nanomaterial and its piezoelectric photocatalytic application, characterized in that The preparation method comprises the following steps: Step 1, weigh 20.0-25.0g of sodium hydroxide and 0.8-1.0g of titanium dioxide, respectively, dissolve and disperse them in 50ml of distilled water, and form a uniform solution by ultrasonication; stir at room temperature for 2 hours, transfer the mixed solution to the lining of the reactor for hydrothermal reaction, and centrifuge the turbid liquid after the hydrothermal reaction to obtain a certain amount of precipitate; Step 2: Soak the precipitate obtained in step 1 in a dilute hydrochloric acid solution for 8 hours, then centrifuge and wash with water three times, and finally wash with ethanol, and vacuum dry to obtain H2Ti3O7 powder; Step 3: Weigh 0.15-0.2g of the powder obtained in step 2 and 0.3-0.5g of barium hydroxide octahydrate, disperse and dissolve them in 50ml of distilled water, and form a uniform solution by ultrasonication; transfer the mixed solution to the lining of the reactor for hydrothermal reaction, and centrifuge the turbid liquid after the hydrothermal reaction to obtain a certain amount of precipitate; Step 4: Soak the precipitate obtained in step 3 in a dilute hydrochloric acid solution for 8 hours, then centrifuge and wash with water three times, and finally wash with ethanol, and vacuum dry to obtain barium titanate nanomaterials; Step 5: Dissolve 0.3-0.4g sodium molybdate and 0.7-0.8g thiourea in 80ml distilled water, and form a uniform transparent colorless solution by ultrasonication. Add the barium titanate powder obtained in step 4, stir for 1.5 hours, adjust the pH, transfer the mixed solution to the lining of the reactor for hydrothermal reaction, and centrifuge the turbid liquid after the hydrothermal reaction to obtain a certain amount of precipitate. Step 6: Wash the precipitate obtained in step 5 with water, centrifuge, alternately three times, and finally wash with ethanol, and vacuum dry to obtain a molybdenum disulfide-coated barium titanate nanocomposite material.

2. The method according to claim 1, characterized in that: The hydrothermal reaction temperature in step 1 is 180-200° C., preferably 200° C.; the hydrothermal reaction time is 18-24 h, preferably 24 h; The centrifugal speed in step 1 is 9000 r / min.

3. The method according to claim 1, characterized in that: The centrifugal speed in step 2 is 9000 r / min; The vacuum drying conditions in step 2 are: temperature of 50 to 70°C, preferably 60°C; vacuum degree of -25 to -30 kPa, preferably -30 kPa; time of 9 to 14 h, preferably 12 h.

4. The method according to claim 1, characterized in that: The hydrothermal reaction temperature in step 3 is 180-220°C, preferably 210°C; the hydrothermal reaction time is 85 min; The centrifugal speed in steps 3, 4, 5 and 6 is 9000 r / min.

5. The method according to claim 1, characterized in that: The hydrothermal reaction temperature in step 5 is 180-220° C., preferably 220° C.; the hydrothermal reaction time is 24-30 h, preferably 30 h; The pH value of step 5 is adjusted to 0.5-2, preferably 1.

5.

6. A molybdenum disulfide-coated barium titanate nanomaterial prepared by the method of claims 1 to 5.

7. The use of the molybdenum disulfide-coated barium titanate nanomaterial in piezoelectric photocatalytic degradation of organic pollutants according to claim 6, characterized in that The specific steps are as follows: evenly disperse the molybdenum disulfide-coated barium titanate nanomaterial in the organic pollutant Rhodamine B aqueous solution, stir in the dark to reach adsorption and desorption equilibrium, measure the absorbance change of the Rhodamine B aqueous solution under mechanical force and light conditions using a liquid ultraviolet visible spectrophotometer, and finally calculate the degradation rate of the Rhodamine B aqueous solution.

8. The method according to claim 7, characterized in that: The concentration of rhodamine B (RhB) solution is 20 mg / L; the mechanical force and light are generated by ultrasound and xenon lamp irradiation, the ultrasound frequency is 40 kHz, the xenon lamp power is 300 W, and the filter is: λ>420 nm.

9. The use of the molybdenum disulfide-coated barium titanate nanomaterial in piezoelectric-photocatalytic water decomposition to produce hydrogen according to claim 6, characterized in that The specific steps are as follows: first, the molybdenum disulfide-coated barium titanate nanomaterial is evenly dispersed in a triethanolamine aqueous solution, and then the mixed solution is poured into a closed container, nitrogen is introduced, and oxygen is excluded. Under the combined action of mechanical force and light, the amount of hydrogen produced is measured by a gas chromatograph.

10. The method according to claim 9, characterized in that: The mechanical force and light are generated by ultrasound and xenon lamp irradiation, wherein the ultrasound frequency is 40 kHz, the xenon lamp power is 300 W, and the filter is: λ>420 nm; and the volume fraction of the triethanolamine aqueous solution is 20%.

Citation Information

Cited By

  • Piezoelectric core-shell heterojunction capable of producing hydrogen peroxide as well as preparation method and application of piezoelectric core-shell heterojunction

    CN122321912A